THE IMPACT OF CO-CURRICULAR ACTIVITIES ON THE OVERALL PERFORMANCE OF SECONDARY SCHOOL STUDENTS IN FATA - Muhammad Ashfaq; Dr. Soniha Aslam; Syed Asim Hussain (The Sky)
The study was aimed to analyze the relationship of co-curricular activities with academic progress, personality development and leadership skills of Male Secondary School students of FATA. A sample size of 200 respondents was selected on the basis of random sampling technique. The study was delimited to Qirat, Naat, Sports, Scouting, Quiz and Speech contest. A questionnaire of five points Likert Scale after seeking due permission from Principals and Head Masters was used to reach to the in-depth of the phenomena. Statistical techniques Mean, Percentage and Standard Deviation were run to analyze the collected data. The researcher analyzed the relationship between co-curricular involvement and its positive impacts on students overall performances. Finally it was determined that co-curricular activities has a durable connection with physical and mental health, self-confidence, qualities of leadership, personality development, interpersonal relationship, personal hygiene, healthy behaviors and educational performances.